The ancient port of Arikamedu : new excavations and researches, 1989-1992 - Begley, Vimala, 1931-; Arikamedu Excavation Project; Ecole francais d'Extreme-Orient (Pondicherry, India). Centre d'histoire et d'archeologie. (Pondichery : Centre d'histoire et d'archeologie, Ecole francaise d'Extreme-Orient, 1996)
Results of archaeological excavations at Arikamedu, near Pondicherry, of Podouke (Extinct city).
'The Arikamadu [i.e. Arikamedu] Excavation Project (1989-92) of the University Museum, University of Pen[n]sylvania, in collaboration with Madras University, was carried out under the auspices of the American Institute of Indian Studies and was funded by grants from the Smithsonian Institution'--Vol. 1, t.p. verso.
Folded plan in pocket at end of v. 1.
Includes bibliographical references (v. 1, p. [ix]-xv) and index.
Keywords: Excavations (Archaeology) -- Podouke (Extinct city); Romans -- Podouke (Extinct city); Podouke (Extinct city)